2003
DOI: 10.1093/pcp/pcg025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Citrate Transport through the Plasma Membrane in a Carrot Mutant Cell Line with Enhanced Citrate Excretion

Abstract: ;The superior ability of citrate excretion in a carrot (Daucus carota L.) mutant cell line, namely IPG (insoluble phosphate grower) [Takita et al. (1999a) Plant Cell Physiol. 40: 489] cells has been characterized in terms of citrate transport at the plasma membrane. IPG cells released about a 20-fold increase in citrate in comparison with malate, while the concentration of malate was only 35% lower than that of citrate in the cell sap. Citrate excretion was sensitive to anion channel blockers, such as niflumic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…Plant culture and malate excretion were carried out under aseptic conditions. Malate concentrations in the medium were measured by an enzymatic cycling method according to Hampp, Goller & Füllgraf (1984) with minor modifications as described previously (Ohno, Koyama & Hara 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Plant culture and malate excretion were carried out under aseptic conditions. Malate concentrations in the medium were measured by an enzymatic cycling method according to Hampp, Goller & Füllgraf (1984) with minor modifications as described previously (Ohno, Koyama & Hara 2003).…”
Section: Methodsmentioning
confidence: 99%
“…At this point some speculation was made as to the possible weak acid identity but, as well as for SA and GABA, none of the other main organic acids known to be secreted to the apoplast under stress conditions seemed to fit with the inhibitor's characteristics. In fact, the finding that in all experimental conditions so far tested no link between activity state of the PM H + ‐pump and apoplastic inhibitor concentration was detected suggested that the inhibitor could not apparently match with either AA or citrate, whose excretion was proved to be closely linked to the PM H + ‐ATPase activity (Ohno et al 2003, Ryan et al 2001, Takahama 1996, Tomasi et al 2009). Also, the possibility that the FC‐induced increase in apoplastic H 2 O 2 content might result from an inhibiting effect of malate on catalase activity seemed quite unlikely, given that its production too is known to be strictly correlated to the activity state of the PM H + ‐ATPase (Beffagna and Romani 1994, Marrè et al 1987).…”
Section: Resultsmentioning
confidence: 98%
“…An important role for citrate excretion into the apoplast in response to environmental stresses such as P i deficiency and exposure to high Al 3+ levels was also established. Furthermore, as well as for AA, the activity state of the PM H + ‐ATPase was proved to be correlated with the release of this organic acid from cells, an increased activity of this enzyme being accompanied by an enhanced citrate excretion (Ohno et al 2003, Ryan et al 2001, Tomasi et al 2009). And else, an increase in salicylic acid (SA) synthesis was proved to be induced by FC (Schaller et al 2000, Singh and Roberts 2004) and this molecule, proposed as the putative endogenous signal for systemic‐acquired resistance (Malamy et al 1990, Mètraux et al 1990), was suggested to act by binding to and inhibiting a catalase (Chen et al 1993, Dempsey and Klessig 1994).…”
Section: Introductionmentioning
confidence: 93%
“…PM fractions were isolated and purified by the procedures described by Ohno et al with some modification [6]. Briefly, aloe callus were chopped with a scalpel and homogenized in cold (4°C) grinding buffer (pH 7.8) (3 ml/g fresh weight) containing 25 mM potassium phosphate buffer (pH 7.8), 0.25 M mannitol, 1.5% (w/v) polyvinylpyrrolidone, 0.1% (w/v) bovine serum albumin (BSA, fatty acid free, Sigma), 1 mM dithiothreitol (DTT), 2 mM EGTA and 2 mM EDTA-2Na, using a mortar and pestle.…”
Section: Preparation Of Plasma Membranementioning
confidence: 99%